Direct Product of SP-Algebra - Murugappan, Mullai (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
In this paper, properties of SP-Algebra have been investigated and direct product of SP-Algebra has been introduced and some theorems were stated and proved.